(a - b - c)^2 Formula
What Is (a - b - c)2 Formula?
We just read that by multiplying (a - b - c) by itself we can easily derive the (a - b - c)2 formula. Let us see the expansion of (a - b - c)2 formula. (a - b - c)2 = (a - b - c)(a - b - c) (a - b - c)2 = a2 - ab - ac - ab + b2 + bc - ca + bc + c2 (a - b - c)2 = a2 + b2 + c2 - 2ab + 2bc - 2ca (a - b - c)2 = a2 + b2 + c2 - 2(ab - bc + ca)Let us see how to use the (a - b - c)2 formula in the following section.
Examples on (a - b - c)2 Formula
Let us take a look at a few examples to better understand the formula of (a - b - c)2.Example 1: Find the value of (a - b - c)2 if a = 2, b = 4, and c = 3 using (a - b - c)2 formula. Solution:To find: (a - b - c)2 Given that: a = 2, b = 4, c = 3 Using ...
Bạn đã thích câu chuyện này ?
Hãy chia sẻ bằng cách nhấn vào nút bên trên
Truy cập trang web của chúng tôi và xem tất cả các bài viết khác!